Dielectric Loss Suppression of Silver/Poly(vinylidene fluoride) Composite Films with Polydopamine. Issue 4 (3rd April 2018) - Hu, Die; Jiang, Ming; Hou, Yan; Zhang, Jingjing; Fang, Dong; Liu, Lei; Huang, Jing; Li, Hairong; Xiong, Chuanxi
ABSTRACT: The preparation and dielectric properties of silver-polydopamine/poly(vinylidene fluoride) (Ag-PDOP/PVDF) composite films with suppressed dielectric loss are reported. The dielectric loss tangents of the composite films were found to be rather low similar to that of pure PVDF over the frequency range 100 Hz to 30 kHz, almost regardless of the Ag content, and even lower than that of pristine PVDF in the relatively high frequency region. The nanoscale structure comprised of Ag nanoparticles (Ag NPs), isolated by the PDOP coating and the PVDF matrix, hindered the formation of percolative networks, resulting in the decreased conduction loss in the composite films, even at a high filler loading. The strong interfacial interaction between the Ag@PDOP particles and the PVDF matrix also contributed to the restrained interfacial loss. Consequently, these composite films had higher permittivity and smaller dielectric loss than the PVDF matrix at relatively high frequencies, and would thus be attractive for physically small capacitor applications in electronics and electric power systems.